Vote Buying in Indonesia The Mechanics of Electoral Bribery - Muhtadi, Burhanuddin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
Muhtadi$1 (Bs analysis of vote-buying in post-democratization Indonesia is original, profound, subtle, nuanced, and convincing as well as beautifully organized and well written. Equally important, its imaginative policy prescriptions will be widely read and cited as a significant contribution to the literature of comparative electoral politics. $1 (BWilliam Liddle, Ohio State University, USA This book presents a pathbreaking analysis of vote-buying in Indonesia. Drawing on a stunning array of evidence, Muhtadi reveals the mechanics, patterns and effects of vote-buying with unprecedented clarity. [Title] is a must read for anyone interested in Indonesian politics or in the comparative politics of clientelism. $1 (BEdward Aspinall, Australian National University, Australia This book contains a trove of interesting research questions, a novel theoretical contribution, impressive empirical work, and a deep and nuanced understanding of the Indonesian case. $1 (BAllen Hicken, University of Michigan, USA This book is open access under a CC BY 4.0 license. This book investigates the impact of vote buying on the accountability of democratic institutions and policy representation in newly democratic countries, with a focus on Indonesia. In doing so, the book presents a wide-ranging study of the dynamics of vote buying in Indonesia$1 (Bs young democracy, exploring the nature, extent, determinants, targeting and effectiveness of this practice. It addresses these central issues in the context of comparative studies of vote buying, arguing that although party loyalists are disproportionately targeted in vote buying efforts, in total numbers$1 (Bgiven the relatively small number of party loyalists in Indonesia$1 (Bvote buying hits more uncommitted voters. It also demonstrates that the effectiveness of vote buying on vote choice is in the 10 percent range, which is sufficient for many candidates to secure a seat and thus explains why they still engage in vote buying despite high levels of leakage. Burhanuddin Muhtadi is a lecturer at State Islamic University, Jakarta. He is also an executive director of Indonesian Political Indicator and Director of Public Affairs at Indonesian Survey Institute (LSI). He has published his articles in numerous scholarly journals.s
1. Introduction -- 2. The Prevalence of Vote Buying in Indonesia: Building an Index -- 3. The Determinants of Vote Buying: The Profile of Typical Vote 'Sellers' -- 4. Do Candidates Target Loyal or Swing Voters? Beyond the Core- versus Swing Voter Debate -- 5. How Targeting Goes Astray: Explaining the Gap between Intentions and Outcomes -- 6. Vote Brokerage, Personal Networks, and Agency Loss -- 7. Does Vote Buying Affect Voting Behaviour? Chasing Winning Margins and the Prisoner's Dilemma -- 8. Conclusion.
Keywords: Elections; Asia -- Politics and government; Electoral Politics; Asian Politics